2017
DOI: 10.15446/agron.colomb.v35n2.61894
|View full text |Cite
|
Sign up to set email alerts
|

Technological factors associated with oil palm yield gaps in the Central Region in Colombia

Abstract: Factores tecnológicos asociados a las brechas en el rendimiento en cultivos de palma de aceite de la Zona Central en Colombia Elizabeth Ruiz A. 1 , Eloina Mesa F. 1 , Mauricio Mosquera M. 1 , and Juan Carlos Barrientos F. ABSTRACT RESUMENThis study builds on the results from a previous study (Ruiz, 2017), aimed to identify and quantify yield gaps in a sample of lots from small and medium scale producers, all suppliers of the same mill. The technical staff from the mill provides technical assistance to the afor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…
Adopting technology regarding agricultural crops has traditionally been associated with high costs. Producers have thus often abstained from adopting better agronomical practices and have consequently lost the benefits they could otherwise have obtained by implementing better criteria for managing their crops.This research builds on results by Ruiz et al, (2017) who found three typologies of oil palm lots, regarding adoption of technology and yields on oil palm crops from Colombia. This work was aimed at evaluating the typologies found by Ruiz et al (2017) from an economic standpoint by using different economic assessment methods, in order to determine the benefits of technology adoption at the Colombian oil palm agroindustry.
…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…
Adopting technology regarding agricultural crops has traditionally been associated with high costs. Producers have thus often abstained from adopting better agronomical practices and have consequently lost the benefits they could otherwise have obtained by implementing better criteria for managing their crops.This research builds on results by Ruiz et al, (2017) who found three typologies of oil palm lots, regarding adoption of technology and yields on oil palm crops from Colombia. This work was aimed at evaluating the typologies found by Ruiz et al (2017) from an economic standpoint by using different economic assessment methods, in order to determine the benefits of technology adoption at the Colombian oil palm agroindustry.
…”
mentioning
confidence: 87%
“…Producers have thus often abstained from adopting better agronomical practices and have consequently lost the benefits they could otherwise have obtained by implementing better criteria for managing their crops.This research builds on results by Ruiz et al, (2017) who found three typologies of oil palm lots, regarding adoption of technology and yields on oil palm crops from Colombia. This work was aimed at evaluating the typologies found by Ruiz et al (2017) from an economic standpoint by using different economic assessment methods, in order to determine the benefits of technology adoption at the Colombian oil palm agroindustry. The methods used were aimed at estimating: unit cost, net present value (NPV), net income, land use efficiency, generation of income and competitiveness.Results indicate that the cost of producing a ton of fresh fruit bunches from oil palms (FFB) on lots having high adoption of technology was 2.5% to 8% lower when compared to lots having lower adoption of technology (Typologies 2 and 3. respectively).…”
mentioning
confidence: 87%
See 3 more Smart Citations